Manajemen Koinfeksi Malaria Berat dengan HIV Belum Mendapat Terapi Antiretrovirus di Era Pandemi COVID-19: Sebuah Laporan Kasus - Harijanto, Paul; Mawuntu, Rosye; Rusli, Novia; Adiwinata, Randy; Nugroho, Agung (UI Scholars Hub, 2023)
Severe malaria is a serious infectious disease that required immediate diagnosis and prompt treatment. Severe malaria may result several organ failures which is similar with other infectious diseases like SARS-CoV-2, sepsis, dengue, and HIV infection. Most of those infection have similar symptoms such as fever, myalgia, and headache, therefore physician should have high suspicion regarding co-infection with other infectious agents. The overlapping symptoms of co-infections may become a challenge for physician in diagnosing and delivering prompt therapy. Failure to deliver prompt treatment may lead to fatal outcome such as in severe malaria case. Stigmatization of all patients with fever and cough for COVID-19, may lead to misdiagnosis, moreover in some facilities which SARS-COV-2 PCR testing may not readily available to rule out infection. Therefore, it is importance to have broad differential diagnosis of fever during COVID-19 pandemic era, including the possibility of malaria infection in immunocompromised patients This can be achieved by comprehensive history taking and physical examination in evaluating patients with fever. We report antiretroviral naïve HIV infected patient with severe malaria indicated by several multi organ damage that successfully treated.